Discourse of Khakot Lampung Dance as A Political Technology of The Body to Make Individuals Obedient - Jamil, Sulhan; Kasiyan, Kasiyan (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
This article examines the role of traditional Khakot dance in Lampung as a discourse of political technology that influences the body to make individuals obedient to the values and social cultural norms of Lampung. This research focused on three issues. First, the form of representation of the body that complies with the social values and norms of Lampung culture in Khakot dance. Second, the process of forming a body that abides by the social values and norms of Lampung culture in Khakot dance. Third, identifying factors that influence individual compliance with sociocultural values and norms in the context of Khakot dance. This study used a critical discourse analysis paradigm and utilized primary and secondary data. Analysis of all obtained data was carried out textually and contextually using Michel Foucault's body discipline theory which is presented in a qualitative descriptive form. The results showed that the representation of the body that obeys the social values and norms of Lampung culture is reflected in aspects of Khakot dance performances, including the selection of costume forms and choreographic forms such as movement and floor pattern composition. The process of forming the body to be obedient to the social values and norms of Lampung culture in the context of Khakot dance involves formal and non-formal education, as well as through sociocultural activities in Lampung society. Factors that influence individual compliance are social control, normalization, and panopticon.